RANCANG BANGUN TRAINER HOME AUTOMATION MENGGUNAKAN MODUL NODE MCU ESP8266 BERBASIS INTERNET OF THINGS (IoT) - Atmiasri; Maharani Wisudawati Swista Rani (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2022)
The development of knowledge and technology in the world of education is currently advancing rapidly, providing many new ideas, methods and innovations in the field of technology development, especially trainers. Home automation is the introduction of technology in a home environment to provide convenience and protection for residents by remote monitoring. The smart home modeling device based on the ESP8266 Node MCU and the Internet of Things (IoT) uses Blynk as a monitoring controller that is stored on a Virtual Private Server (VPS). This system uses relays to connect lights, sockets, and fans, the DHT11 Sensor detects humidity and temperature, the Flame Sensor detects fire, and the MQ-2 Sensor detects gas leaks. The results obtained that the average lag time for turning on the relay is about 0.12 seconds and the average turning off the relay is about 0.12 seconds, the average error of the DHT11 Sensor when detecting heat is 3.3O Celsius and when detecting cold is -28.2O Celsius, the limit for detecting fire on the Flame Sensor is a maximum of 20 cm, the limit for gas leakage is set above 200 ppm.